How We SEE Is How We Learn: Reflection in the Workplace. Issue 3 (August 2020) - Kowalski, Rita; Russell, Cynthia
The Problem: Today's workers face constant economic, social, scientific, and technological change — a challenging climate for learning. Learners need to integrate and balance acting, reflecting, thinking, and feeling as they negotiate within this everchanging environment. The Solution: This Special Issue explores workplace learning's power through the understanding and application of reflective practices which are often informal and incidental and occur as individuals engage and learn from the experience of their daily activities. The Stakeholders: HRD scholars and practitioners will benefit from an understanding of the tools and practices that facilitate workplace learning through reflection. This Special Issue provides a theoretical framing of workplace reflection, situates reflection in various contexts, offers examples of use in the workplace, addresses its risks, and raises questions for both research and practice.